2016
DOI: 10.3389/fnbeh.2016.00186
|View full text |Cite
|
Sign up to set email alerts
|

Microglomerular Synaptic Complexes in the Sky-Compass Network of the Honeybee Connect Parallel Pathways from the Anterior Optic Tubercle to the Central Complex

Abstract: While the ability of honeybees to navigate relying on sky-compass information has been investigated in a large number of behavioral studies, the underlying neuronal system has so far received less attention. The sky-compass pathway has recently been described from its input region, the dorsal rim area (DRA) of the compound eye, to the anterior optic tubercle (AOTU). The aim of this study is to reveal the connection from the AOTU to the central complex (CX). For this purpose, we investigated the anatomy of larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 73 publications
(127 reference statements)
5
73
0
Order By: Relevance
“…In desert locusts, double labeling showed that two types of TL neurons, TL2 and TL3 are GABA‐immunoreactive (Homberg et al, ). Similar neurons have been identified in the field cricket (Sakura et al, 2008), the monarch butterfly (Heinze et al, ; Heinze & Reppert, ), a dung beetle (el Jundi et al, ), and two species of bees (Held et al, ; Stone et al, ). In the fruit fly, corresponding neurons were termed ring neurons (R‐neurons), based on their ring‐like innervation pattern in the ellipsoid body, and five subtypes R1–R5 were distinguished connecting the bulb with the ellipsoid body (Hanesch et al, 1989; Omoto et al, ).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In desert locusts, double labeling showed that two types of TL neurons, TL2 and TL3 are GABA‐immunoreactive (Homberg et al, ). Similar neurons have been identified in the field cricket (Sakura et al, 2008), the monarch butterfly (Heinze et al, ; Heinze & Reppert, ), a dung beetle (el Jundi et al, ), and two species of bees (Held et al, ; Stone et al, ). In the fruit fly, corresponding neurons were termed ring neurons (R‐neurons), based on their ring‐like innervation pattern in the ellipsoid body, and five subtypes R1–R5 were distinguished connecting the bulb with the ellipsoid body (Hanesch et al, 1989; Omoto et al, ).…”
Section: Discussionmentioning
confidence: 57%
“…Detailed analysis in the locust Schistocerca gregaria , the fly Drosophila melanogaster , and the moth Manduca sexta identified tangential neurons of the CBL (termed TL neurons in locusts, R neurons in flies) to be immunostained. These neurons have dendritic arborizations in microglomerular complexes in the bulbs, small areas in the lateral complex (Held et al, ; Schmitt, Stieb, Wehner, & Rössler, ; Träger, Wagner, Bausenwein, & Homberg, ). In addition, in all species studied, the CBU showed sparse GABA immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Signals are transferred via a specific pathway to the CBL (Homberg et al, 2003; Pfeiffer and Kinoshita, 2012; Held et al, 2016; Schmitt et al, 2016). In the desert locust, three types of tangential neuron to the CBL, termed TL1, TL2, and TL3 neurons provide polarization signals to the central complex (Vitzthum et al, 2002; Heinze et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…If these neurons do not form synapses in both glomeruli, no information can be received or sent by the neurons. Therefore, axonal projections forming synapses with dendrites in the same glomerulus has become a basic assumption and has also been demonstrated in various Drosophila studies (Träger et al, 2008; Olsen et al, 2010; Held et al, 2016). It has also been shown in the central complex (Lin C.-Y.…”
Section: Methodsmentioning
confidence: 85%